Properties of Polymer-Composite Used as Fills of Asian Lacquerware: Issues on Restoration Processes of Lacquered Objects from Cultural Heritage - Anne-Solenn Le Hô; Isabelle Fabre-Francke; Caroline Thiphavong (International Journal of Polymer Science)
One of the common problems encountered in lacquerware issued from cultural heritage is the appearance of lifting areas and some losses of material. Composite systems made of commercial polymer and different fills were tested as filling agents for the cracking, splitting, and losses compensation of Asian lacquer. For that purpose, the stability of traditional and modern commercially available materials usually used in the restoration practice of historical lacquerware was assessed. Their thermomechanical and chemical properties and surface state were evaluated by a set of techniques (TGA, DMA, mechanical test, contact angle value, and microtopography). There is a drastic change of the behavior of the interface between fill and Asian lacquer, dependent on the nature of the composite fillers. So the evaluation of materials and processes for the restoration of Asian lacquer were emphasized. The commercial Paraloid B72 used with glass microspheres as additives appeared to be the most stable of all of the investigated fillers.